2019
DOI: 10.35530/it.070.01.1532
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly route for dyeing of cotton fabric using three organic mordants in reactive dyes

Abstract: The textile dyes and fixing agents that used in dyeing process are major contributor to environmental pollution. In the present study, three different organic mordants (Sodium Citrate, Ammonium Acetate, and Potassium Acetate) are used in exhaust dyeing as mordants. Effect of mordant concentrations is studied on fastness properties (color change, rubbing fastness & light fastness) of cotton dyed with reactive dyes using these organic mordants. Comparison of these mordants with conventional fixing agent (NaC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Some organic compounds are used directly as organic mordant agents in reactive dyes. Baig et al ( 2019 ) used sodium citrate, ammonium acetate, and potassium acetate as organic mordants in their study. It is reported that out of these three salts, sodium citrate demonstrated superior fastness characteristics in comparison to other salts, while organic salts displayed greater K/S ratios at lower concentrations.…”
Section: Mordant Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some organic compounds are used directly as organic mordant agents in reactive dyes. Baig et al ( 2019 ) used sodium citrate, ammonium acetate, and potassium acetate as organic mordants in their study. It is reported that out of these three salts, sodium citrate demonstrated superior fastness characteristics in comparison to other salts, while organic salts displayed greater K/S ratios at lower concentrations.…”
Section: Mordant Agentsmentioning
confidence: 99%
“…Baig et al ( 2019 ) used sodium citrate, ammonium acetate, and potassium acetate as mordants in their studies. In the study, sodium citrate outperformed other salts in terms of its fastness properties, while organic salts displayed better K/S ratios at lower concentrations.…”
Section: Mordant Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Some chemicals, such as heavy metals, organic dyes and alkalis, may cause toxic impacts on biological health and ecological safety. 2 As necessities in our daily life, textiles and apparel products are in great demand, 3 which inevitably increases the consumption of textile chemicals and the amount of chemical pollutants discharged into the environment. Therefore, chemical management and control in the production processes of textiles and apparel products is very important, and it is essential to establish an effective environmental impact assessment method for textile chemicals.…”
mentioning
confidence: 99%